ISOLATION AND IDENTIFICATION OF ESCHERICHIA COLI FROM BROILERS AND LAYERS IN NAMAKKAL - S. Deepadharshini; G. Selvaraju; S. Saravanan; K. Sukumar (Indian Journal of Veterinary and Animal Sciences Research, 2026)
A study was undertaken to isolate, identify and determine the prevalence of Escherichia coli in broilers and layers in Namakkal, a major poultry production hub in South India. A total of 200 samples were collected aseptically, consisting of 100 broiler meat samples obtained from retail outlets and 100 cloacal swabs collected from commercial layer farms. Isolation was carried out using standard cultural procedures, followed bybiochemical characterization to confirm presumptive E. coli. Molecular identification was performed by targeting the 16S rRNA gene. All 129 isolates that were presumptively identified as E. coli yielded the expected 410 bp amplicon, validating the accuracy of phenotypic identification. The prevalence of E. coli was 66.00 per cent in broiler meat samples, indicating considerable contamination at the retail level and emphasizing the need for improved hygienic handling and processing practices. In layer birds, 63.00 per centpositivity in cloacal swabs reflected persistent intestinal carriage and the potential for environmental dissemination. Overall, the findings demonstrate a high occurrence of E. coli across different stages of the poultry chain and underline the importance of continuous microbiological surveillance to support food safety, guided intervention strategies and reduced public health risks.